The Impact of the Coronavirus Crisis on Revenues of Hotel and Restaurant Businesses in Bulgaria - Marinov, Marin; Todorova, Lyubomira (Dr. Viktor Koval, 2022)
Introduction. The changes that have taken place in the global economy as a result of the coronavirus pandemic have had a negative impact on all economic sectors. The most negative manifestation of this is in the tourism industry. Bulgarian tourism is also among those hit hard by the crisis. This is evidenced by the many bankruptcies of travel companies and the reported financial difficulties. Many of the restrictions imposed on tourists when crossing national borders and the requirements for those wishing to use tourist services are just some of the reasons for the crisis in the sector. Its deepening is the basis for making recommendations to correct the situation. The reasons for the current study are the problems in the tourism sector and the threatening trends of frequent corporate bankruptcies, as well as the closure of many tourist sites. Aim and tasks. The aim of the study is to present the situation in which the economic entities of the tourism sector in the Republic of Bulgaria operate and to propose solutions for improving their financial and economic condition. The scope of the study used data for various indicators (visits of foreign tourists, overnight stays of Bulgarian and foreign citizens, turnover indices in the sector, etc.) describing the state of Bulgarian tourism for the period 2019–2021. Results. The processed data given an idea of the current state of the tourism sector in the Republic of Bulgaria. The study is a corrective to the problems in the industry, which are provoked by changes in the visits of local and foreign tourists. Based on the analysis, a set of recommendations were made to improve the state of the sector: achieving sustainability of tourist visits; stricter requirements for transport companies; provision of financial assistance by the government; opportunities to use the interest-free grace period for received loans; and establishing Bulgaria as a safe destination. Conclusion. The conducted situational analysis of the hotel and restaurant business in Bulgaria for the period 2019-2021 is the basis for making several recommendations aimed at stabilizing the sector. Some of them are related to: financial support for the tourism business given by the state; reducing the rate of tax due; ensuring an interest-free grace period for loans from financial institutions; providing opportunities for using funds under various programs for the implementation of innovations in the activities of tourism companies in order to increase their competitiveness and bring them into a state that meets national and world requirements for tourism business.